Annual reports in computational chemistry. - Dixon, David A. (ISSN, 2019)
Annual Reports in Computational Chemistry, Volume 15, provides timely and critical reviews of important topics in computational chemistry. Topics covered in this series include quantum chemistry, molecular mechanics, force fields, chemical education, and applications in academic and industrial settings. Focusing on the most recent literature and advances in the field, each article covers a specific topic of importance to computational chemists. Key Features: Includes timely discussions on quantum chemistry and molecular mechanics; Covers force fields, chemical education, and more; Presents the latest in chemical education and applications in both academic and industrial settings. Readership: Researchers and students interested in computational chemistry as well as computational chemists and chemists interested in using computational approaches to address chemical problems. --